PENGARUH PROFITABILITAS, LIKUIDITAS DAN CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Rosalia, Yuliesti; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Tax is one of the revenue sources for the country. Therefore, tax revenue becomes the larger contribution ofstate revenue and expenditure. For the company, tax is considered as the burden which will decrease the profit ofthe company. It has made the company try to find a way to decrease the tax cost. This research is meant to testthe influence of return on assets, current ratio, institutional ownership, independent commissioner, auditquality, and audit committee to the tax avoidance. This research is quantitative research. The population is StateOwned Enterprises (BUMN) which are listed in Indonesia Stock Exchange (IDX), meanwhile the sample is havebeen selected by using purposive sampling technique and 64 companies have been selected as samples. The resultof this research shows that: (1) return on asset does not have any influence to the tax avoidance; (2) current ratiodoes not have any influence to the tax avoidance; (3) institutional ownership has negative influence to the taxavoidance; (4) independent commissioner has negative influence to the tax avoidance; (5) audit quality does nothave any influence to the tax avoidance; (6) audit committee does not have any influence to the tax avoidance.Keywords: Profitability, liquidity, corporate governance, tax avoidance.